PENGGUNAAN GAYA BAHASA KIASAN DALAM “KOMENTAR: DEMOKRATIE IST MEHR ALS NUR EIN #HASHTAG” DITINJAU DARI PRINSIP KESANTUNAN - Dini Tian Puspita (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2017)
This study is aimed to give description about the use of allegory in order to know its politeness principle. They shown from news article Deutsche Welle titled Komentar: Demokratie ist mehr als nur ein #Hashtag. The problems encountered in the field are: there is not only an allegory that could be shown up but also from pragmatic side, which is maxims of politeness principle. Thus, the problems are formulated as follow: 1)What kind of allegory that shown in the article? 2)How is the use of allegory from its maxims of politeness principle in the article?. The kind of study is descriptive that uses qualitative approach. The subject of study is one news article. The result of study shown that are irony, sarcasm and satire in allegory and also one retoric style. It also shown how they allow and also break the maxims of politeness principle The conclusion is the news shown how the writer talk loudly with her irony, sarcasm, satire and retoricsm style that break the pragmatics maxims of politeness principle. The youth still do not get into Brexit even the government has announce the referendum itself.